Penguatan Kompetensi Literasi dan Kesadaran Kultural melalui Pelatihan Menulis Cerita Rakyat pada Siswa SMA Negeri 1 Rasau Jaya - Kristoforus Bagas Romualdi; Reyhan Ainun Yafi; I Ketut Arya Sentana Mahartha (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to address the low level of fiction writing skills and the declining interest of the younger generation in preserving local culture at SMA Negeri 1 Rasau Jaya. The program was implemented using a classical training approach that included theoretical presentations, writing practice, and intensive mentoring. The results indicate an improvement in literacy competence, as evidenced by the success of the majority of students in composing complete folktale manuscripts and presenting them in front of the class. Based on participants’ evaluations, the program was effective in overcoming technical writing difficulties while also fostering cultural awareness to preserve the oral traditions of West Kalimantan.